Key Factors Affecting Weed Seeds' Germination, Weed Emergence, and Their Possible Role for the Efficacy of False Seedbed Technique as Weed Management Practice - Travlos, Ilias; Gazoulis, Ioannis; Kanatas, Panagiotis; Tsekoura, Anastasia; Zannopoulos, Stavros; Papastylianou, Panayiota (Frontiers in Agronomy, 2020)
Important parameters that influence weed seeds' germination and seedlings' emergence can also affect the efficacy of false seedbed as weed management practice. These parameters consist of environmental factors such as soil temperature, soil water potential, exposure to light, fluctuating temperatures, nitrates concentration, soil pH, and the gaseous environment of the soil. Soil temperature and soil water potential can exert a great influence on composition of the weed flora of a cultivated area. Base soil temperatures and base water potential for germination vary among different weed species and their values can possibly be used to predict which weeds will emerge in a field as well as the timing of emergence. Predicting the main flush of weeds in the field could maximize the efficacy of false seedbed technique as weed management practice. Timing, depth, and type of tillage are important factors affecting weed emergence and, subsequently, the efficacy of false seedbed. The importance of shallow tillage as a weed control method in the false seedbed technique has been highlighted. Further research is needed to understand and explain all the factors that can affect weed emergence so as to maximize the effectiveness of eco-friendly weed management practices such as false seedbed in different soils and under various climatic conditions.